Distribution and Seasonal Variation of Total Metals in Surface Water of the Tennessee River Basin - Okweye, Paul; Golson-Garner, Karnita (International Journal of Bio-resource and Stress Management, 2023)
Heavy metals in surface water were measured to determine their distribution and seasonal variations in Flint Creek and Flint River watersheds. Bi-weekly stream water samples were collected from six selected sites within the watersheds. The samples were digested using an approved EPA method SW 846-3015 in a closed vessel microwave and analyzed for total recoverable metals of some selected elements of concern ( Al, Co, Ni, Cu, Fe, Mn, Cd, As, Se, Zn, Pb, and P), using ICP-OES (Perkin-Elmer Optima 2100 DV series). Heavy metal concentrations ranged from undetectable to 123 μg l-1 (Pb), 409 μg l-1 (Al), and 453 μg l-1 (Zn). Physical and chemical water quality parameters including heavy metal concentrations were also measured. The concentration ranges of all the metals measured were mostly below the EPA guidelines for acceptable concentrations for drinking water, except Al, Pb, Fe and P. The water quality parameter shows that the dissolved oxygen (DO) concentrations in three of the sites are very low (<5 mg l-1) and could affect aquatic organisms. All metals were statistically significant (at p≤0.05) by watershed. Patterns observed were a steady increment in metal concentrations from upstream to downstream in both watersheds. The seasonal variation was also evident that the rivers had higher heavy metal content (>45%) during winter and spring than summer and fall. Results suggested that agriculture, past and present land use practices, have resulted in significant adverse impacts on the study areas